Cladophialophora bantiana Brain Abscess in an Immunocompetent Patient - Sanjay G. Revankar (Canadian Journal of Infectious Diseases and Medical Microbiology)
Cladophialophora bantiana is a dematiaceous mold with a predilection for causing central nervous system infection, particularly in normal hosts. A case involving a 79-year-old immunocompetent woman who presented with left-sided weakness and a ring-enhancing brain lesion is reported. She underwent surgical excision, which revealed a brain abscess due to C bantiana. The patient was treated with liposomal amphotericin B for several weeks, then switched to voriconazole and flucytosine, but eventually succumbed to the infection. Therapy is not standardized for this rare mycosis, and mortality remains high, even in immunocompetent patients. Additional studies to understand the pathogenesis of this infection and to improve outcomes are needed.